Age, hepatitis C virus infection, and the risk of cancer: Unlocking a complex puzzle of interactions. Issue 7 (24th January 2017) - Li, Daneng; Hurria, Arti
Abstract : Hepatitis C infection may increase the risk of various malignancies among older adults. A better understanding of the complex biology of the aging process and hepatitis C infection may help to unlock an important piece of the puzzle in the world of cancer development. See also pages 1202‐11.